Meningkatkan Motivasi dan Kemampuan Penguasaan Konsep Siswa Pada Materi Struktur Jaringan Tumbuhan dan Hewan Melalui Media Biology Quartet Card - Halida, Ane Nitra; Windyariani, Sistiana (FKIP Universitas Muhammadiyah Sukabumi, 2019)
Increasing Motivation and Ability to Mastery Students' Concepts on Material Structure of Plant and Animal Networks Through Media Biology Quartet Card (BQC). This study aims to improve the motivation and mastery of students' concepts in the material structure of plant and animal tissue in class XI SMA using the media Biology Quartet Card (BQC). The research method is Classroom Action Research with two cycles. The research subjects were 32 students in class XI IPA of SMAN 4 Kota Sukabumi. The research instrument uses motivation questionnaires as well as questions about mastery of concepts with multiple choice questions. The results showed that the average student motivation was 73.5% in participating in learning using BQC. As for the acquisition of the concept mastery value, the average in the first cycle was 48.08 and the second cycle increased to 70.41.